MEASURING ENTREPRENEURSHIP INTENTION OF FEMALE STUDENTS AT TELKOM UNIVERSITY - Adellia Hartono (Business Journal : Jurnal Bisnis Dan Sosial, 2022)
This study aims to determine the effect of interest in entrepreneurial intentions. This research is a survey research using a questionnaire as an instrument. The population used in this study were college students at Telkom University and West Java university students. The sample used was Telkom University undergraduate students and 100 respondents were selected using the purposive sampling method, which is a sample selection technique where an individual chooses a sample based on a personal assessment of some appropriate characteristics of the sample members. The instrument validity test uses Confirmatory Factor Analysis, while the reliability test uses Cronbach Alpha. The analysis technique used is multiple regression analysis.